PRAGMASEMANTICS ANALYSIS OF COMMERCIALADVERTISEMENTS IN THE AMERICAN FASHION INDUSTRY - Alwan Maulana; Ahmad Zaenal Abidin; Tatu Siti Rohbiah (PT. Intelek Cendikiawan Nusantara, 2025)
In the era of globalization and the development of communication technology, commercial advertising has become one of the main means of shapping public perception of brands and products, especially in the highly competitive and dynamic fashion industry of the United States. Advertising in this industry serves not only as a promotional tool, but also as a complex communication medium that relies on language to influence, persuade, and bulid brand identity. Therefore, understanding the meaning behind advertising messages is important to explore the communication strategies used. Pragmasemantics analysis, which combines the study of meaning (semantics) with the use of language in a social (pragmatic) context, offers a critical approach to understanding how advertising messages are design to produce a particular effect on audiences. This approach allows analysis not only of the literal meaning of the advertising text, but also of the implicit meanings, assumptions, implications, and persuasive strategies used to influence consumers. The fashion industry in America is known not only for its products, but also for its advertising-built naratives-naratives that are often loaded with symbolism, lifestyle, and cultural values. Thus, analyzing advertising from a pragmatic perspective becomes essential to understand how meaning is constructed and how consumers are targeted linguistically and psychologically. This study also contributes to broader discussion in linguistics and media studies by demonstrating how language in advertising reflects and reinforce social ideologies, aspirations, and consumers identity in a globalized marketplace. Through a pragmasemantics lens, this research reveals the power of linguistics choises in shaping emotional engagement, creating desire, and aligning consumer behaviour with brand ideologies.